PREVELANCE, RISK FACTORS AND OUTCOMES OF HYPOGLYCEMIA IN ELDERLY DIABETIC PATIENTS - Shah, Nazir; Amanullah, Amanullah; Afridi, Mohammad Hussain; Jamal, Sheraz; Marwat, Mumtaz Ali (Journal of Postgraduate Medical Institute, 2012)
Objective: To estimate the clinical outcomes of hypoglycemia in elderly diabetic patients, its associations with the different antidiabetic drugs and some predisposing factors or comorbid conditions. Methodology: Both type 1 and type 2 diabetic patients with age 60 years or above fulfilling Whiple's criteria for hypoglycemia were included in this study. They were collected from the medical unit Hayatabad Medical Complex Peshawar from November 2010 to July 2011. The patient's history, clinical examination and investigations were recorded on a proforma. Patients with abnormal CNS findings on CT or MRI scan and those who didn't give any partial or complete response to the IV glucose, were excluded from the study. Results: Eighty five patients with mean age of 75+6 years were included in this study. The average hospital stay was 10 days. Sixty-five percent (n=55) of these patients were using sulfonylureas, 20% (n=17) were using metformin alone and in combination, while 25% (n=21) were using insulin (combination of regular & intermediate acting). Impaired renal function in 40% (n=34), impaired liver functions in 20% (n=17) and neglected elderly in 30.6% (n=26) were the most common predisposing factors. Conclusion: Diabetic treatment related hypoglycemia is more severe in the elderly population with a poor prognosis. Sulfonylureas are the most frequently associated drugs with poorer outcomes. Predisposing factors like impaired renal functions, liver functions and neglected elderly increase the frequency of hypoglycemia. HbA1c is not a good predictor of hypoglycemia in elderly population.